Higher Order Thinking Skills in Mathematics with Project Based Learning - Ndiung, Sabina; Merlin Atika Street; Mariana Jediut (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This research was conducted to overcome teachers' problems in integrating learning activities oriented towards higher level thinking which until now has not been a priority. This research aims to analyze creative thinking skills and mathematical problem solving abilities through the application of a project-based learning model. This research uses a quantitative approach with a quasi-experiment method with posttest-only group design. The sample consisted of 53 grade V elementary school students consisting of two classes with details of the experimental class totaling 27 people and the control class totaling 26 people using random sampling techniques. Data collection techniques use test techniques. The tests used are descriptive tests both to measure creative thinking skills and for data about problem solving abilities. Based on the reliability test results, all items are in the high category. The data analysis technique uses MANOVA with the help of SPSS 23.00. Research findings show that both separately and simultaneously the creative thinking abilities and problem solving abilities of students who receive learning using the project-based learning model are higher than students who receive learning using the conventional model. Implications of this research shows that project-based learning (PBL) can improve students' abilities in critical, creative, analytical thinking and complex problem solving.